Influence of Third Party Funds, BI Rate, Inflation On Market Share In Islamic Banking - Aziz Septiatin (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2022)
The market share that can be controlled by Islamic banking is still relatively small compared to conventional banking, so this study aims to examine the influence of third party funds, BI Rate and Inflation on the share of Islamic banking in Indonesia for the 2015-2021 period. The sample in this study uses a saturated sampling technique, which means that the entire population is sampled, both Islamic commercial banks and sharia business units registered with the Financial Services Authority. The method of data analysis in this study used the classical assumption test, multiple linear regression analysis and hypothesis testing. The results showed that third party funds and the BI Rate had an effect on market share, while inflation had no effect on market share. Simultaneously, third party funds, BI Rate and Inflation have a significant influence on market share. The overall contribution of the independent variable to the dependent variable is 87.7%.